Znaki zapytania - Sokorski, Wlodzimierz (Warszawa : Instytut Wydawn. Zwiazkow Zawodowych, 1988)
A contemporary story in the bleak days after Martial Law in Poland.
Keywords: Poland -- History -- 1980-1989 -- Fiction